1991
DOI: 10.1128/aac.35.3.512
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to pefloxacin in Pseudomonas aeruginosa

Abstract: Mechanisms of resistance to pefloxacin were investigated in four isogenic Pseudomonas aeruginosa strains: S (parent isolate; MIC, 2 ,ug/ml), PT1 and PT2 (posttherapy isolates obtained in animals; MICs, 32 and 128 ,ug/ml, respectively), and PT2-r (posttherapy isolate obtained after six in vitro subpassages of PT2; MIC, 32 ,ug/ml). [2-3H]adenine incorporation (indirect evidence of DNA gyrase activity) in EDTA-permeabilized cells was less affected by pefloxacin in PT2 and PT2-r (50% inhibitory concentration, 0.27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
(51 reference statements)
2
15
0
Order By: Relevance
“…We also tested a strain of P. aeruginosa with altered permeability due to reduced expression of Omp D2 combined with increased amount of lipopolysaccharides in the outer membrane. These alterations more markedly reduced the activity of quinolones than did deficiency of OmpF, which confirms our recent observation that both Omp D2 and lipo-polysaccharides are involved in the diffusion of quinolones through the outer membrane (Michea-Hamzehpour et al, 1991). Interestingly, we observed that in a P. aeruginosa strain with only a mutated DNA gyrase, similar changes in the MICs of quinolones were seen as observed for E. cloacae.…”
Section: Discussionsupporting
confidence: 78%
“…We also tested a strain of P. aeruginosa with altered permeability due to reduced expression of Omp D2 combined with increased amount of lipopolysaccharides in the outer membrane. These alterations more markedly reduced the activity of quinolones than did deficiency of OmpF, which confirms our recent observation that both Omp D2 and lipo-polysaccharides are involved in the diffusion of quinolones through the outer membrane (Michea-Hamzehpour et al, 1991). Interestingly, we observed that in a P. aeruginosa strain with only a mutated DNA gyrase, similar changes in the MICs of quinolones were seen as observed for E. cloacae.…”
Section: Discussionsupporting
confidence: 78%
“…This indicates the importance of utilizing truly isogenic strains obtained without direct antibiotic selection. Other authors have also suggested a role for OprD in uptake of quinolones (16,17) or other antibiotics (24) in P. aeruginosa. These conclusions are based in part on poorly defined clinical or experimental animal isolates or on in vitro model liposome swelling experiments that have been criticized on other grounds (3,31,33).…”
Section: Discussionmentioning
confidence: 99%
“…Some, but not all, fluoroquinolone-resistant mutants are cross resistant to imipenem and lack OprD. For example, Michea-Hamzehpour et al demonstrated that decreased fluoroquinolone susceptibility was associated with a decrease or loss of OprD and proposed that OprD can catalyze the facilitated diffusion of fluoroquinolone as it does for imipenem (16,17).…”
mentioning
confidence: 99%
“…While several strains with decreased susceptibilities to several agents have been isolated, which suggests a mutation in nalB, there are biochemical differences that are commensurate with different mutations encoding multiple resistance. Some quinolone-resistant P. aeruginosa strains contain a new 54-kDa outer membrane protein (14, 18) or lack a 31.5-kDa outer membrane protein (9, 17), possibly OprF, or have decreased levels of proteins D2 and Hi or Gl (5,20,23). Several workers have also reported changes in lipopolysaccharide (LPS) (6,18,34).…”
mentioning
confidence: 97%
“…Many laboratory mutants contain alleles of nalB and require nalidixic acid MICs of >500 ,ug/ml and are cross resistant to carbenicillin, ureidopenicillins, chloramphenicol, and novobiocin (33, 34). Resistant strains have arisen during experimental P. aeruginosa infections, with several classes of mutants isolated with mutations resembling naL4 and nfxC (10,22,23). Quinolone-resistant P. aeruginosa isolated from patients may also have the nal4 or nalB phenotype (43) or a nalB-like phenotype lacking OprF.…”
mentioning
confidence: 99%